Phase-lag synchronization analysis in complex systems with directed inter-relations - Martins, V. S. G.; Rodrigues, A. C.; Cerdeira, H. A. [UNESP]; Machado, B. S. (Springer, 2016)
In this work, we proposed a novel way to estimate phase-lag synchronization in coupled systems. This approach was applied into two systems: a directed-coupled Rossler-Lorenz system and a network of Izhikevich neurons. For the former case, the phase-lag synchronization revealed an increase in complexity for the Lorenz subsystem components, when the coupling is activated. The opposite behavior was observed when the Izhikevich network were organized in a hierarchical way. Our results point out to emergent synchronism related to causal interactions in coupled complex systems.